Stimulasi Kreativitas Anak Usia Dini melalui Pembelajaran STEAM Berbasis Media Loosparts: Tinjauan Naratif Sistematis - Qoumariah, Siti; Mustapa, Noviana; Aisyah, Siti; Ulfah, St. Maria; Chandrawati, Titi (Pendidikan Guru PAUD Universitas Persatuan Guru Republik Indonesia Semarang, 2025)
The integration of STEAM (Science, Technology, Engineering, Art, and Mathematics) learning in Early Childhood Education is increasingly recognized as essential for cultivating 21st-century skills. This systematic narrative review explores how STEAM learning, when combined with loose parts media, stimulates creativity in early childhood. A total of 515 articles were initially identified through four databases (ProQuest, ERIC, Open Knowledge Map, and Elicit) covering the years 2019–2024. After applying strict inclusion and exclusion criteria, eight peer-reviewed studies were selected for analysis. These studies vary in method, including qualitative, quasi-experimental, and review-based designs, and focus on children aged 3–6 years. The review reveals that loose parts media flexible, open-ended materials enhance key dimensions of creativity such as imagination, originality, problem-solving, collaboration, and innovation when implemented within the STEAM framework. Children engaged in these activities exhibit higher levels of critical thinking and exploratory learning. The findings also highlight the importance of teacher facilitation, cultural context, and long-term developmental impact. This review enriches both practical and theoretical understanding of creative learning strategies based on loose parts within the STEAM framework in early childhood education. It contributes new insights by synthesizing studies that explicitly connect both components, which are often examined separately. Educators and policymakers are encouraged to incorporate this integrative approach into early learning environments to maximize children’s cognitive and creative growth.